Recurrent chromosomal rearrangements of ROS1, FRK and IL6 activating JAK/STAT pathway in inflammatory hepatocellular adenomas. Issue 9 (6th January 2020) - Bayard, Quentin; Caruso, Stefano; Couchy, Gabrielle; Rebouissou, Sandra; Bioulac Sage, Paulette; Balabaud, Charles; Paradis, Valerie; Sturm, Nathalie; de Muret, Anne; Guettier, Catherine; Bonsang, Benjamin; Copie, Christiane; et al.
Abstract : Background: Inflammatory hepatocellular adenomas (IHCAs) are benign liver tumours characterised by an activation of the janus kinase (JAK)/signal transducers and activators of transcription (STAT) pathway caused by oncogenic activating mutations. However, a subset of IHCA lacks of identified mutation explaining the inflammatory phenotype. Methods: 657 hepatocellular adenomas developed in 504 patients were analysed for gene expression of 17 genes and for mutations in seven genes by sequencing. 22 non-mutated IHCAs were analysed by whole-exome and/or RNA sequencing. Results: We identified 296 IHCA (45%), 81% of them were mutated in either IL6ST (61%), FRK (8%), STAT3 (5%), GNAS (3%) or JAK1 (2%). Among non-mutated IHCA, RNA sequencing identified recurrent chromosome rearrangement involving ROS1, FRK or IL6 genes. ROS1 fusions were identified in 8 IHCA, involving C-terminal part of genes highly expressed in the liver ( PLG, RBP4, APOB ) fused with exon 33–35 to 43 of ROS1 including the tyrosine kinase domain. In two cases a truncated ROS1 transcript from exon 36 to 43 was identified. ROS1 rearrangements were validated by fluorescence in situ hybridisation (FISH) and led to ROS1 overexpression. Among the 5 IHCA with FRK rearrangements, 5 different partners were identified ( MIA3, MIA2, LMO7, PLEKHA5, SEC16B ) fused to a common region in FRK that included exon 3–8. No overexpression of FRK transcript was detected but the predicted chimeric proteins lacked the auto-inhibitory SH2–SH3 domains. In two IHCA, we identified truncated 3'UTR of IL6 associated with overexpression of the transcript. Conclusion: Recurrent chromosomal alterations involving ROS1, FRK or IL6 genes lead to activation of the JAK/STAT pathway in IHCAs.